RESPONS PERTUMBUHAN TEMBAKAU DELI (Nicotiana tabaccum (L.)) PADA BEBERAPA JENIS KAPUR DAN TANAH DI SUMATERA UTARA - Martua M Silaban; Jonis Ginting; Asil Barusd (Jurnal Agroekoteknologi, 2013)
Response of growth of deli tobacco (Nicotiana tabaccum (L.)) on  some kind of lime and  soil types in North Sumatera. Deli tobacco is variety of tobacco that is used as world top quality wrapper of cigar . But, in last years production of deli tobacco had been decreasing because of land degradation. Consequently, it is important to develop deli tobacco plantation to another soil types that is combine by giving some kind of lime. The aim of this research was to examine growth of deli tobacco (Nicotiana tabaccum (L.)) on some kind of lime and soil types in Noerth Sumatera.  The research was conducted in the land of the Research Center of Deli Tobacco (BPTD) Sampali PTPN II, starting from February to May 2012, using a randomized block design (RBD) factorial with two factors and three replications . The first factor is soil types  (alluvial, andosol, hidromorf, ultisol). The second factor is the kind of lime  (dolomite, calsit, kaptan). The results showed that soil types significantly affect on plant height, diameter of stem, number of leave, thick leaf sand,          1 foot thick leaves, long leaves sand, 1 foot long leaves, leaf width sand, and 1 foot wide leaves. Kind of Lime and the interaction between soil and lime is not significantly affect for all parameter observed.   Keywords: soil, lime, Tobacco Deli.